Evidence for scale‐ and disturbance‐dependent trait assembly patterns in dry semi‐natural grasslands. (1st August 2013) - de Bello, Francesco; Vandewalle, Marie; Reitalu, Triin; Lepš, Jan; Prentice, Honor C.; Lavorel, Sandra; Sykes, Martin T.; Vesk, Peter
Summary The mechanisms driving nonrandom assembly patterns in plant communities have long been of interest in ecological research. Competing ecological theories predict that coexisting species may either be more functionally dissimilar than expected by chance (with functional 'divergence' mainly reflecting niche differentiation) or be functionally more similar than expected (with functional 'convergence' reflecting either the outcome of environmental filtering or weaker‐competitor exclusion effects). Assembly patterns are usually assessed at a single scale and disturbance regime, whereas considering different spatial scales and disturbance regimes may clarify the underlying assembly mechanisms. We tested the prediction that convergence and divergence are scale‐ and disturbance‐ dependent in grazed and abandoned species‐rich dry grasslands within a 22 km2 landscape in south‐eastern Sweden. Convergence and divergence were tested for plant species' traits and phylogenetic relationships at three nested spatial scales: within 412 plots (50 × 50 cm, divided into 10 × 10 cm subplots), within 117 grassland patches (from 0.02 to 11.63 ha) and within the whole landscape (across patches). At the finest scale (10 × 10 cm subplots within plots), coexisting species were more different than expected by chance (divergence), both functionally and phylogenetically, suggesting niche differentiation. At the intermediate scale (50 × 50 cm plots within patches), coexisting species showed convergence, suggesting environmental filtering. No significant deviations from random expectations were detected at the broadest scale (patches within the 22 km2 landscape) – suggesting the prevalence of dispersal limitation at this scale. The fact that nonrandom patterns were particularly evident under grazed conditions is consistent with the prediction that assembly patterns are disturbance dependent. Synthesis. This study shows that multiple trait‐based assembly processes operate simultaneously in species‐rich communities, across spatial scales and disturbance regimes. The results support earlier theoretical predictions that divergence between coexisting species may be an important driver of community assembly, particularly at finer spatial scales, where species compete for the same local resources. In contrast, environmental filtering is expected at broader spatial scales, where species growing in particular environmental conditions share traits that are adaptive under those conditions. Within given habitat types, dispersal limitation may, however, override environmental filtering at increasing spatial scales of observation.